Correlation Between Serum β2-GPI/oxLDL and the Risk of Cerebral Infarction in Patients with T2DM - Kuang, Wending; Li, Yi; Liu, Gang; Zhang, Yang; Chen, Gang; Luo, Bang; Kuang, Shuangyu (Frontiers in Surgery, 2022)
Objective To study the correlation between serum β2-glycoprotein I (β2-GPI)/oxidized low-density lipoprotein (oxLDL) and the risk of cerebral infarction in patients with type 2 diabetes (T2DM). Methods From January 2019 to March 2021, 56 patients with T2DM combined with cerebral infarction were chosen as diabetic cerebral infarction (DCI) group, and 60 patients with simple T2DM were chosen as T2DM group. In addition, 60 healthy volunteers were recruited as a control group. Collect the essential information of each group, and compare the serum β2-GPI/oxLDL and inflammatory factor levels in each group. The clinical factors that affect the risk of ischemic cerebral infarction in patients with T2DM was analyzed by a logistic model. Results Compared with the control group, the level of serum β2-GPI/oxLDL in the T2DM and DCI groups increased significantly, P<0.001. Compared with the T2DM group, the serum β2-GPI/oxLDL level in the DCI group increased significantly, P<0.05. The result of Pearson correlation analysis showed that serum β2-GPI/oxLDL was positively correlated with total cholesterol, triglycerides, fasting blood glucose, 2h postprandial blood glucose, glycosylated hemoglobin, interleukin-6, and tumor necrosis factor (TNF)-α (all P <0.05). Serum TNF-α and β2-GPI/oxLDL were independent risk variates for DCI (P<0.05). Based on the receiver operating characteristic curve analysis, the area under the curve for TNF-α, serum β2-GPI/oxLDL and the combined diagnosis of DCI were 0.653 (0.552~0.753), 0.680 (0.583~0.777), 0.739 (0.647~0.831). Conclusion In DCI patients, the levels of serum oxLDL/β2-GPI is significantly increased. Serum oxLDL/β2-GPI is an independent risk factor which affects the occurrence of DCI. In addition, serum β2-GPI/oxLDL level implicates the lipid metabolism and inflammatory status of the internal environment of DCI patients in a certain extent.